Диплоидно-полиплоидный комплекс С. auratus carassius карповых рыб (Cyprinidae) в фауне Украины - Межжерин, С.В.; Кокодий, С.В. (Видавничий дім "Академперіодика" НАН України, 2007)
Proofs are given of the existence of a hybrid association of crucian carps that are presented by diploid C. carassius, С. auratus and triploid C. carassius, С. auratus species, and also triploid С. auratus-С. gibelio, di-, tri- and tetraploid C. auratus carassius and triploid C. carassius species hybrids. The key features of C. auratus carassius hybrids are their bisexual structure, males and diploid females fertility, and the limited reproduction capacity of tri- and tetraploid females. The cyto- and morphometric descriptions of hybrid forms and paternal species are given, and the phenodeviations that are much more frequently discovered within hybrids are analyzed.